Biomarkers for Diagnosing Febrile Illness in Immunocompromised Children: A Systematic Review of the Literature - van der Velden, Fabian J. S.; Gennery, Andrew R.; Emonts, Marieke (Frontiers in Pediatrics, 2022)
Objective To assess the performance of biomarkers used for the prediction of bacterial, viral and fungal infection in immunocompromised children upon presentation with fever. Methods We performed a literature search using PubMed and MEDLINE and In-Process & Other Non-Indexed Citations databases. Cohort and case-control studies assessing biomarkers for the prediction of bacterial, viral or fungal infection in immunocompromised children versus conventional microbiological investigations were eligible. Studies including adult patients were eligible if paediatric data were separately assessable. Data on definitions used for infections, fever and neutropenia, and predictive values were collected. Risk of bias was assessed with the Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) tool. Results Fifty-two studies involving 13,939 febrile episodes in 7059 children were included. 92.2% were in cancer patients (n=48), 15.7% also included haematopoietic stem cell transplantation patients (n=8). Forty-three biomarkers were investigated, of which 6 (CRP, PCT, IL-8, IL-6, IL-10, TNFα) were significantly associated with bacterial infection at admission, studied in multiple studies, and provided predictive data. Literature on prediction of viral and fungal infection was too limited. Eight studies compared CRP and PCT, with PCT demonstrating superiority in 5. IL-6, IL-8 and IL-10 were compared with CRP in six, four and one study respectively, with mixed results on diagnostic superiority. No clear superior biomarker was identified comparing PCT versus IL-6, IL-8 or IL-10. Discussion There is great heterogeneity in biomarkers studied, cut-off values and definitions used, complicating analysis. Literature for immunocompromised children with non-malignant disease and for non-bacterial infection is sparse. Literature on novel diagnostics was not available. We illustrated the challenges of diagnosing fever adequately in this study population and the need for improved biomarkers and clinical decision-making tools.